(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the historical, etymological, and semantic dimensions of the Homeland concept in both Uzbek and English languages by analyzing various explanatory sources. In particular, the term Vatan in Uzbek originates from Arabic and denotes "motherland" or "native land," while the English lexeme homeland is shown to have derived from ancient Greek and Germanic roots. Furthermore, like in many other languages, this lexeme is distinguished by a rich and diverse set of synonyms that deeply reflect the emotional connection to one’s birthplace and homeland.